Penerapan Terapi Murottal Terhadap Perubahan Perilaku Kekerasan Klien Skizofrenia di RSJD Dr. RM. Soedjarwadi Klaten Provinsi Jawa Tengah - Siti Putri Yuliana; Sitti Rahma Soleman; Wahyu Reknoningsih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The risk of violent behavior is a response to the stressor faced by someone who is shown by violent behavior both to himself and to other people and the environment both verbally and non-verbally. One way to reduce the impact of violent behavior is by giving murottal therapy. Objective; To find out the results of implementing the Murottal Therapy Application for Changes in the Violent Behavior of Schizophrenic Clients at RSJD Dr. RM. Soedjarwadi, Central Java Province. Method; This type of research is a case study using descriptive research methods. Results; The score for violent behavior change for 2 respondents before the murottal therapy was carried out was at the intensive stage score 2, which means that at the moderate behavior change stage where client 1 got a score of 11 while client 2 got a score of 14. The score for the change in violent behavior for 2 respondents after murottal therapy was at the stage score intensive 3 which means at the stage of mild behavior change where client 1 gets a score of 8 while client 2 gets a score of 9. There are differences in changes in violent behavior in respondents with a risk of violent behavior before and after the murottal therapy intervention. Conclusion; There are differences in changes in violent behavior before and after murottal therapy in patients at risk for violent behavior.